Renal Function and Risk Stratification of Patients With Embolic Stroke of Undetermined Source. Issue 12 (December 2018) - Ntaios, George; Lip, Gregory Y.H.; Lambrou, Dimitris; Michel, Patrik; Perlepe, Kalliopi; Eskandari, Ashraf; Nannoni, Stefania; Sirimarco, Gaia; Strambo, Davide; Vemmos, Konstantinos; Koroboki, Eleni; Manios, Efstathios; et al.
Abstract : Background and Purpose—: We aimed to assess if renal function can aid in risk stratification for ischemic stroke or transient ischemic attack (TIA) recurrence and death in patients with embolic stroke of undetermined source (ESUS). Methods—: We pooled 12 ESUS datasets from Europe and America. Renal function was evaluated using the estimated glomerular filtration rate (eGFR) and analyzed in continuous, binary, and categorical way. Cox-regression analyses assessed if renal function was independently associated with the risk for ischemic stroke/TIA recurrence and death. The Kaplan-Meier product limit method estimated the cumulative probability of ischemic stroke/TIA recurrence and death. Results—: In 1530 patients with ESUS followed for 3260 patient-years, there were 237 recurrences (15.9%) and 201 deaths (13.4%), corresponding to 7.3 ischemic stroke/TIA recurrences and 5.6 deaths per 100 patient-years, respectively. Renal function was not associated with the risk for ischemic stroke/TIA recurrence when forced into the final multivariate model, regardless if it was analyzed as continuous (hazard ratio, 1.00; 95% CI, 0.99–1.00 for every 1 mL/min), binary (hazard ratio, 1.27; 95% CI, 0.87–1.73) or categorical covariate (likelihood-ratio test 2.59, P =0.63 for stroke recurrence). The probability of ischemic stroke/TIA recurrence across stages of renal function was 11.9% for eGFR ≥90, 16.6% for eGFR 60–89, 21.7% for eGFR 45–59, 19.2% for eGFR 30–44, and 24.9% for eGFR <30 (likelihood-ratio test 2.59, P =0.63). The results were similar for the outcome of death. Conclusions—: The present study is the largest pooled individual patient-level ESUS dataset, and does not provide evidence that renal function can be used to stratify the risk of ischemic stroke/TIA recurrence or death in patients with ESUS.